Edukasi Alat Pelindung Diri (APD) Pada Pengrajin Perak di kelurahan Borong Kota Makassar - Suharni Suharni; Poetri Lestari Lokapitasari; Hukma Ratu Purnama; Alfina Baharuddin; Yuliati Yuliati; Fatma Jama; Yuliana Yuliana (Window of Community Dedication Journal, 2026)
Personal protective equipment (PPE) is equipment used to protect workers from accidents or illnesses caused by contact with potential hazards in the work environment, whether physical, chemical, or biological. Exposure routes include the respiratory system, skin, mouth, and eyes. Silver artisans are among the UMKM groups at risk of occupational diseases. Therefore, the use of PPE is crucial. This community service activity was conducted at the home of the head of the silver artisans’ association in Borong Village, Makassar City. The participants consisted of 15 artisans. The results of this activity showed an increase in knowledge between the pre- and post-tests, with an average score of 89%; an improvement in attitude between the pre- and post-tests, with an average score of 87%; and an improvement in the partners’ behavior between the pre- and post-tests, with an average score of 90%. It is hoped that similar educational activities should be conducted periodically to reinforce behavioral changes and raise artisans’ awareness regarding the use of PPE, consistently applying OSH principles in all work activities, particularly the use of personal protective equipment (PPE) and ergonomic work postures. Actively participate in training and follow-up mentoring activities to further enhance knowledge and skills in maintaining occupational health.